The Pan-African French press and the socio-political evolution of Cabinda conflict from 1970 to 1980 : case of Jeune Afrique and Afrique-Asie - (:unkn) unknown (My University, 2013)
The province of Cabinda, included to Angola since 1975, claims for autonomy. The history tells us about its status as a Portuguese protectorate; what contributed to the blossoming of the cultural and social specifities of the Cabinda people. This status was ignored at the Angolan independence with as consequence the absorption of Cabinda, highly coveted because its kerosene and other mineral resources. In the 1970s, the province of Cabinda was involved into a civil war extremely deadly. We have kept this temporal setting to see the way two magazines of the African Press, Jeune Afrique and Afrique-Asie, reported about the war andwe have simultaneously analyzed through a set of published articles the way journalists have reported about Cabinda. This dissertation throws light on the disinterest of the French-speaking Pan African Press about the sociopolitical situation of Cabinda.
Keywords: African Research